A PHYLOGENETIC ANALYSIS OF FASCIOLARIIDAE (GASTROPODA: BUCCINOIDEA) - Couto, Diogo Ribeiro do (2017)
The neogastropod family Fasciolariidae comprise of important representatives of tropical and subtropical molluscan assemblages, with over 500 species in the subfamilies Fasciolariinae, Fusininae and Peristerniinae. Fasciolariids with many well-known species such as tulip shells, horse-conchs, spindles, among others have a long complicated taxonomical history, with several genus names being used to group heterogeneous contingents of many unrelated species. Recently, however, taxonomical revisions have begun to set straight its taxonomy. The present work aims to resolve the phylogeny of the family Fasciolariidae, through: 1) a morphological phylogenetic parsimony analysis in TnT based on 95 characters and 53 taxa which revealed a monophyletic Fasciolariidae, with the genera Dolicholatirus and Teralatirus representing the first split in the family, followed by three splits that correspond to a fusinine grade, which also include the genus Pseudolatirus (Peristerniinae); a last split groups the peristerniine genera Peristernia and Fusolatirus, while the last group comprises of fasciolariines and the remaining peristerniines. None of these clades correspond to the present-day accepted circumscription of the three recognized subfamilies. 2) Complementing the work of Couto et al. (2016), which used a five-gene molecular dataset to analyze the phylogeny of the family. To this dataset, the previous morphological matrix was added, generating a total evidence dataset that was implemented in POY. This analysis revealed a non-monophyletic family with the genera Dolicholatirus and Teralatirus as non-fasciolariids; the remaining fasciolariids are well-supported, with the first split a monophyletic Fusininae and Pseudolatirus; a second split groups Peristernia and Fusolatirus; while the last, the remaining peristerniines and fasciolariines. Total evidence was congruent with the morphological data with the exception of the Fusininae that appeared as a crown-group and not as a grade; Lamellilatirus lamyi (Peristerniinae) nested within the fasciolariines. Finally, 3) supplement the phylogenetic analysis of Simone (2011), inserting the analyzed taxa from the morphological analysis in the same dataset. This resulted in a monophyletic Buccinoidea superfamily, a monophyletic Fasciolariidae, despite low resolution of relationship for internal taxa; Dolicholatirus nested within Fasciolariidae and the fusinines with Pseudolatirus appeared as a monophyletic crown-group.